2019
DOI: 10.1101/867143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Controlling the speed and trajectory of evolution with counterdiabatic driving

Abstract: The pace and unpredictability of evolution are critically relevant in a variety of modern challenges: combating drug resistance in pathogens and cancer 1-3 , understanding how species respond to environmental perturbations like climate change 4, 5 , and developing artificial selection approaches for agriculture 6 . Great progress has been made in quantitative modeling of evolution using fitness landscapes 7-9 , allowing a degree of prediction 10 for future evolutionary histories. Yet fine-grained control of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Finally, while here we have focused on pairwise gene-environment interactions, this study can also inform the development of methods to optimize the scheduling of drug treatments (43,33,36), and to identify higher order antagonistic interactions (47,97), in which the antagonism emerges between three or more genes and/or drugs. We anticipate that applications and generalizations of our approach will contribute to countering antibiotic resistance and advance our understanding of the role of antagonism in cellular networks (98) of multiple organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while here we have focused on pairwise gene-environment interactions, this study can also inform the development of methods to optimize the scheduling of drug treatments (43,33,36), and to identify higher order antagonistic interactions (47,97), in which the antagonism emerges between three or more genes and/or drugs. We anticipate that applications and generalizations of our approach will contribute to countering antibiotic resistance and advance our understanding of the role of antagonism in cellular networks (98) of multiple organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the prevalence of extreme antagonism would address a fundamental question in biology concerning the nature of possible interactions between genes and environmental factors. Furthermore, implementing such environmental factors using antibiotic stressors would offer a pathway to design new antibiotic combinations that exhibit collateral sensitivity, as discussed below, because the action of one antibiotic disfavors the acquisition of resistance to another (30,11,(31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…3, we simulate a persister producing bacteria colony under antibiotic treatment, demonstrating the distinct advantage persisters afford bacteria (10, 14, 17). Our stochastic model of persister production can be used to improve the efficacy of antimicrobial therapies using optimal control from an optimal treatment perspective (52, 5759). Furthermore, recent experimental and mathematical work examines the potential of so-called evolutionarily informed therapy or drug sequencing (53, 54, 60), where a sequence of drugs is administered to sequentially induce susceptibility and overcome drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A subpopulation having a same fitness value is assumed to be homogeneous in terms of how it responds to drug exposure. And, while it has been shown that fitness can often change as a function of drug dose, so called seascapes [31], and that this can be useful for control, we do not consider that possibility here [32].…”
Section: Introductionmentioning
confidence: 99%